2016
DOI: 10.1111/ped.12817
|View full text |Cite
|
Sign up to set email alerts
|

Hemophagocytic lymphohistiocytosis caused by systemic herpes simplex virus type 1 infection: Successful treatment with dexamethasone palmitate

Abstract: Hemophagocytic lymphohistiocytosis (HLH) is a hyperinflammatory condition resulting from an uncontrolled and ineffective immune response. Here, we report a case of HLH caused by disseminated herpes simplex virus (HSV)-1 infection. The patient was initially treated with prednisolone and high-dose acyclovir. Although liver enzymes, coagulation abnormalities, and inflammatory markers were remarkably improved, the platelet count remained low. Prednisolone was therefore switched to dexamethasone palmitate. Thereaft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Studies were excluded if they did not discuss nHLH ( n = 280); aggregated nHLH patient data with all ages ( n = 83); provided insufficient detail and/or data describing a case of nHLH ( n = 28); and for other reasons ( n = 8). Two‐hundred‐five cases of nHLH from 142 articles were included in our analysis 12–152 …”
Section: Resultsmentioning
confidence: 99%
“…Studies were excluded if they did not discuss nHLH ( n = 280); aggregated nHLH patient data with all ages ( n = 83); provided insufficient detail and/or data describing a case of nHLH ( n = 28); and for other reasons ( n = 8). Two‐hundred‐five cases of nHLH from 142 articles were included in our analysis 12–152 …”
Section: Resultsmentioning
confidence: 99%
“…It is well known that systemic infections can lead to complications such as HLH, and several studies have reported viral infections as the leading infectious triggers of HLH [12], [13], [14], [15], [16]. Disseminated HHV-1 infection usually occurs in immunocompromised patients, but has also been described in immunocompetent hosts; reports have described four of five patients with HSV-related HLH as immunocompetent.…”
Section: Discussionmentioning
confidence: 99%
“…As an effective anti-inflammatory drug, limethason is used for treating multiple disorders, including macrophage activation syndrome, hemophagocytic lymphohistiocytosis and idiopathic pulmonary hemosiderosis ( 15 , 17 , 18 ). In addition, Hoshi et al ( 19 ) demonstrated that this drug has a higher treatment rate of rheumatoid arthritis with lower risk of side effects compared with dexamethasone.…”
Section: Discussionmentioning
confidence: 99%